Repeated Courses of Oral Ibuprofen in Premature Infants with Patent Ductus Arteriosus: Efficacy and Safety - Haşim Olgun; Naci Ceviz; İbrahim Kartal; İbrahim Caner; Mehmet Karacan; Ayhan Taştekin; Necip Becit (Elsevier, 2017)
There are limited data about the results of repeated oral ibuprofen (OIBU) treatment. This study aimed to describe patent ductus arteriosus (PDA) closure rates and adverse events after repeated courses of OIBU in premature infants with PDA. Methods: Preterm infants with hemodynamically significant (hs)PDA were enrolled in the study. If the first course of OIBU treatment failed, a second and, if required, third course was administered. Results: A total of 100 patients received OIBU. In six patients, treatment could not be completed due to death (n=3) and side effects (n=3). In three patients, adverse effects related to OIBU (thrombocytopenia and impairment of renal function) developed during the first course. During the second and third courses, no new adverse event occurred. After all courses, the PDA closure rate was determined as 88%. The rate was 71% after the first course, 40% after the second course, and 35% after the third course. Although the second course resulted in a significant increase in the closure rate (p<0.05), the rate did not increase significantly with the third course (p>0.05). The mean postnatal age at the start of the first dose of OIBU was not significantly different among the responders and non-responders to the first course (p>0.05). Clinical characteristics did not affect the closure rate significantly. The number of courses did not have a significant effect on death, when gestational age and birth weight were used as covariates [p=0.867, Exp(B)=0.901, 95% confidence interval=0.264-3.1]. Conclusion: A second course of OIBU seems effective and safe for use in preterm infants with hsPDA. Although a third course of OIBU results in PDA closure in some additional patients, the difference is not significant. Thus, surgical ligation should be considered after the second course, especially in patients with signs of severe heart failure.